The influence of social identity on rural consumers’ intent to shop locally - Rachel A. Addis; Marko Grünhagen (New England Journal of Entrepreneurship, 2014)
Rural consumers’ in- and out-shopping intention has been a research topic for many years. This study investigates the relationship between social identity and rural consumersʼ intent to shop within their local community, along with a number of moderating demographic variables. Using a sample of respondents from the Midwest, this study found a significant and positive relationship between rural consumers who socially identify with people in their local community and their intent to inshop. The influence of several demographic moderators is also explored, and implications for practice and future re-search are discussed.